Association of MTHFR C677T, MTHFR A1298C polymorphism in relation to patients with autism in Thi-Qar Governorate - Roaa M. Nashee; Lamees M. Al-Janabi; Mohammed A. Altahan (Romanian Journal of Neurology)
Background. Recent data suggests that environmental factors may account for up to 40-50% of the variability in the risk of developing autism spectrum disorder (ASD). Aim. The purpose of this study was to examine the correlation between MTHFR polymorphism and the heightened susceptibility to autism in children with autism in Thi-Qar. Material and method. A comparison case-control study of blood samples collected from a cohort of 100 individuals diagnosed with autism, along with 100 healthy individuals serving as a control group. The participants were divided into two groups. The first group, known as the control group, consisted of one hundred healthy people aged between 3 and 14 years. The second group consisted of one hundred autistic patients, ranging in age from 3 to 14 years old. Results. The findings demonstrated a noteworthy elevation in the gene expression of MTHFR C677T and MTHFR A1298C in all groups of patients, in comparison to the control group. The current study showed a significant difference at p-value < 0.05 was recorded the highest genotype was CT in autism patients 85% and in control group 1.43%, while the lowest genotype was TT 5% in autism patients, and in the control group 1.43%. Within the haplotype, a non-significant difference was noted at p-value <0.05, showing that the highest allele was C in the control group at 97.18%, and in autism patients at 51.35%. According to the odds ratio, it showed a significant gene frequency in autism patients than in the control group. The current study showed that a significant difference at p-value <0.05 was recorded in the highest AC genotype in autism patients at 85%, and in the control group 2.86%, while the lowest genotype was CC 4% in autism patients, and in the control group 0%. Within the genotype, a significant different at p-value <0.05 was noted, showing that the highest allele was A in the control group at 97.22%, and T in autism patients at 51.89%. Conclusion. The study data indicates a higher likelihood of ASD in individuals with the MTHFR C677T CT/CC and MTHFR A1298C AC/CC polymorphisms, suggesting a potential involvement of abnormalities in the folate/methylation cycle in autism.